Climate & Food Security Monitoring Bulletin 3rd Quarter 2019 (July – September) - International Water Management Institute; World Food Programme (International Water Management Institute (IWMI). United Nations World Food Programme (WFP)., 2019)
First half of 2019, total rainfall has been below average, despite the fact that June, July and the first ten days of August experienced considerable rainfall, confined mostly to the South-Western Regions. Meteorological forecasts suggest areas in the dry-zone are expected to remain dry through to September. Abnormally dry and moderate drought conditions remain in pockets of North, North-Western, North-Central, Uva and Eastern Provinces. Focus must be placed on risk reduction, adaption measures, and preparedness for drought response interventions; including integrated drought resilience programs to promote improved drought resilience strategies from climate shocks. Surplus Maha (2018/19) and Yala (2019) paddy production means there is no immediate food shortage, and total rice availability is sufficient to meet demand until January 2020 (Department of Agriculture). However, dry conditions and pest attacks in pockets of Kurunagala, Batticaloa, Ampara, Puttalam and Trincomalee caused the destruction of 4,362 ha of paddy. This will not have a major impact on overall paddy production, but will have adverse localised impacts.